2016
DOI: 10.1016/j.ygyno.2016.04.210
|View full text |Cite
|
Sign up to set email alerts
|

The DISINFECT initiative: Decreasing the incidence of surgical INFECTions in gynecologic oncology

Abstract: Background-Surgical site infections (SSI) lead to increased patient morbidity and healthcare costs. Our objective was to decrease the SSI rate following gynecologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…– 15 , 17 –44,46–49,51–59,61–120,122–133,135–140,142–152 The final group of articles also included 3 randomized controlled trials (2.1%), 121,134,141 2 cluster-randomized controlled trials (1.4%), 50,60 and 1 time-series analysis (0.7%). 45 Moreover, 109 studies (75.7%) were performed in high income settings, 8 , 10 12 , 14 , 15 , 17 , 18 , 20 , 21 , 23 30 , 34 –45,47,48,50–53,55–57,60,64–68,72–77,79–82,85–91,93–97,99–101,103–120,122,124–131,134,138,140,143,144,146–152 26 studies (18.1%) were conducted in upper middle income settings, 9 , 13 , 22 , 31 33 ,59,61–63,69–71,78,92,98,102,121,123,132,133,135,137,139,141,145 and 9 studies (6.3%) were conducted in lower middle income countries 19 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…– 15 , 17 –44,46–49,51–59,61–120,122–133,135–140,142–152 The final group of articles also included 3 randomized controlled trials (2.1%), 121,134,141 2 cluster-randomized controlled trials (1.4%), 50,60 and 1 time-series analysis (0.7%). 45 Moreover, 109 studies (75.7%) were performed in high income settings, 8 , 10 12 , 14 , 15 , 17 , 18 , 20 , 21 , 23 30 , 34 –45,47,48,50–53,55–57,60,64–68,72–77,79–82,85–91,93–97,99–101,103–120,122,124–131,134,138,140,143,144,146–152 26 studies (18.1%) were conducted in upper middle income settings, 9 , 13 , 22 , 31 33 ,59,61–63,69–71,78,92,98,102,121,123,132,133,135,137,139,141,145 and 9 studies (6.3%) were conducted in lower middle income countries 19 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3a) 9 11 , 14 , 15 , 17 , 21 , 23 , 29 , 37 , 39 ,51,55,56,65,67,72,77,80,86,88,91,93,94,100,104,105,110,114,117,118,124,130,134,145,147,150 The pooled RR of the before-and-after studies was 0.461 (95% CI, 0.389–0.546), with an overall heterogeneity of I 2 =66.4%. A significant increase of SSI rates associated with a multifaceted intervention (RR, 1.565; 95% CI, 1.015–2.412) was reported in 1 RCT.…”
Section: Resultsmentioning
confidence: 99%
“…5,18 Another possible limitation in the study was the identification used. [19][20][21][22] Notably, SSI rates from the NHSN tend to be lower than those from other sources. Although this might have led to underreporting of the infection rates, the relative decrease in SSI would not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…This system might miss infections that were treated solely on an outpatient basis or superficial SSIs that did not have a microbial culture diagnosis. Studies have shown discrepancies in a hospital’s SSI rates based on the data‐collecting system used 19–22 . Notably, SSI rates from the NHSN tend to be lower than those from other sources.…”
Section: Discussionmentioning
confidence: 99%
“…33 A prospective study of patients undergoing gynecologic surgery found reduced infections at surgical sites and reduced costs among those who used a chlorhexidine wash on the night before surgery compared with a retrospective cohort. 34…”
Section: Antibiotics and Skin Decontaminationmentioning
confidence: 99%